Interim analysis: Open-label extension study of leniolisib for patients with APDS - Rao, V Koneti; Kulm, Elaine; Šedivá, Anna; Plebani, Alessandro; Schuetz, Catharina; Shcherbina, Anna; Dalm, Virgil A; Trizzino, Antonino; Zharankova, Yulia; Webster, Sharon; Orpia, Alanvin; Körholz, Julia; et al. (The Journal of allergy and clinical immunology, 2024)
BACKGROUND: Activated phosphoinositide 3-kinase delta (PI3Kδ) syndrome (APDS; or p110δ-activating mutations causing senescent T cells, lymphadenopathy, and immunodeficiency) is an inborn error of immunity caused by PI3Kδ hyperactivity. Resultant immune deficiency and dysregulation lead to recurrent sinopulmonary infections, herpes viremia, autoimmunity, and lymphoproliferation. OBJECTIVE: Leniolisib, a selective PI3Kδ inhibitor, demonstrated favorable impact on immune cell subsets and lymphoproliferation over placebo in patients with APDS over 12 weeks. Here, we report results from an interim analysis of an ongoing open-label, single-arm extension study. METHODS: Patients with APDS aged 12 years or older who completed NCT02435173 or had previous exposure to PI3Kδ inhibitors were eligible. The primary end point was safety, assessed via investigator-reported adverse events (AEs) and clinical/laboratory evaluations. Secondary and exploratory end points included health-related quality of life, inflammatory markers, frequency of infections, and lymphoproliferation. RESULTS: Between September 2016 and August 2021, 37 patients (median age, 20 years; 42.3% female) were enrolled. Of these 37 patients, 26, 9, and 2 patients had previously received leniolisib, placebo, or other PI3Kδ inhibitors, respectively. At the data cutoff date (December 13, 2021), median leniolisib exposure was 102 weeks. Overall, 32 patients (87%) experienced an AE. Most AEs were grades 1 to 3; none were grade 4. One patient with severe baseline comorbidities experienced a grade 5 AE, determined as unrelated to leniolisib treatment. While on leniolisib, patients had reduced annualized infection rates (P = .004), and reductions in immunoglobulin replacement therapy occurred in 10 of 27 patients. Other observations include reduced lymphadenopathy and splenomegaly, improved cytopenias, and normalized lymphocyte subsets. CONCLUSIONS: Leniolisib was well tolerated and maintained durable outcomes with up to 5 years of exposure in 37 patients with APDS. CLINICALTRIALS: gov identifier: NCT02859727.
Keywords: Class I Phosphatidylinositol 3-Kinases; B cells; primary immunodeficiency; PI3Kδ inhibitor; T cells; clinical trial; mužské pohlaví; mutace; PIK3R1; fosfatidylinositol-3-kinasy třídy I; Adult; mladý dospělý; Phosphatidylinositol 3-Kinases; Immunologic Deficiency Syndromes; syndromy imunologické nedostatečnosti; kvalita života; long-term safety; fosfatidylinositol-3-kinasy; Young Adult; PIK3CD; ženské pohlaví; Mutation; Humans; dospělí; Lymphadenopathy; Female; Quality of Life; APDS; lymfadenopatie; lidé; Male; lymphoproliferation